Morphologic predictors of aortic expansion in chronic type B aortic dissection: $hD. Kotelis, G. Grebe, P. Kraus, M. Müller-Eschner, M. Bischoff, H. von Tengg-Kobligk and D. Böckler - Kotelis, Drosos; Grebe, Garvin; Kraus, P.; Müller-Eschner, Matthias; Bischoff, Moritz; Tengg-Kobligk, Hendrik von; Böckler, Dittmar (Vascular, 2016)
To identify morphologic factors affecting aortic expansion in patients with uncomplicated type B aortic dissections.